Design of a smart anti-theft system for motorbike - Siam, Ahnaf Akif; Bhuiyan, Minhaz Ahemd; Islam, Md. Amirul; Islam, Tasriqul; Muktafi, Nayel (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.